1933
DOI: 10.2307/1414275
|View full text |Cite
|
Sign up to set email alerts
|

An Important Factor in Space Perception in the Peripheral Field of Vision

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1934
1934
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Ferree et al. 9–12 conducted a well‐known study of peripheral refraction along the horizontal meridian out to 60° from fixation in 21 subjects using an objective refractometer. They identified three different patterns of peripheral refraction.…”
Section: Peripheral Refractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferree et al. 9–12 conducted a well‐known study of peripheral refraction along the horizontal meridian out to 60° from fixation in 21 subjects using an objective refractometer. They identified three different patterns of peripheral refraction.…”
Section: Peripheral Refractionmentioning
confidence: 99%
“…This was followed by several studies in the late nineteenth and early twentieth centuries as reported by Ames and Proctor. 8 Ferree et al [9][10][11][12] conducted a well-known study of peripheral refraction along the horizontal meridian out to 60°from fixation in 21 subjects using an objective refractometer. They identified three different patterns of peripheral refraction.…”
Section: Peripheral Refractionmentioning
confidence: 99%